Some notes on taxonomy and distribution of Neotropical Aedokritus Roback and Axarus Roback (Diptera: Chironomidae: Chironominae) - Pinho, Luiz Carlos; Dantas, Galileu P.s.; Hamada, Neusa (Zootaxa, 2019)
Aedokritus platycnemis Edwards, previously known from northeastern Argentina, is redescribed based on holotype and additional material from Brazil. Axarus cordiformis sp. n. is described and figured, based on a male adult collected in Brazilian Amazon. Aedokritus coffeatus Trivinho-Strixino, Aedokritus souzalopesi Oliveira & Messias, Axarus globosus Donato, Mauad & Andersen, Axarus intervales Andersen, Mendes & Hagenlund and Axarus diabolicus Andersen, Mendes & Hagenlund have their distribution extended.